THE ROLE OF ANATOMIC-ULTRASONOGRAPHIC COMPARISON IN THE THYROID GLAND ANATOMY INVESTIGATION - Mota, O.; Halyuk, U.; Slavych, H. (World of Medicine and Biology, 2016)
Since under ultrasonographic examination only certain regions (so-called `acoustic accesses`) are available for scanning, the spacial orientation of examined structures assumes on considerable importance. Futhermore, the interpretation of ultrasonic images is complicated due to the specific location of the thyroid gland (TG) in an inconvenient topographical region and owing to the unusual conditions for investigation from different acoustic accesses. comparisons, they allow us to evaluate the condition of medial and lateral regions of the right and left thyroid gland lobes, study their relationships with the nearest anatomical structures, and visualize the pretracheal lymphatic nodes in case of their increase. The frontal plane anatomic-ultrasonographic comparisons have impact on the objectivity of characteristics of medial and lateral edges of the thyroid gland lobes.